1999
DOI: 10.1016/s0022-5223(99)70098-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac operations in patients with low-grade small lymphocytic malignancies

Abstract: Acceptable outcome may be anticipated after cardiac operations in patients with low-grade chronic lymphocytic leukemia and non-Hodgkin lymphoma in early stages. However, the possibility of infection and progression of cardiac and lymphocytopathologic status in these patients should call for caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…White blood cell count generally increases after open-heart surgery, and CPB may stimulate a leucomoid reaction, which can lead to a relapse in an otherwise quiescent illness 6,7. In our study, white blood cell count increased between acceptable ranges, as seen in Table 1.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…White blood cell count generally increases after open-heart surgery, and CPB may stimulate a leucomoid reaction, which can lead to a relapse in an otherwise quiescent illness 6,7. In our study, white blood cell count increased between acceptable ranges, as seen in Table 1.…”
Section: Discussionsupporting
confidence: 59%
“…CPB, which aggravates cell damage, also has immune-depressant properties, resulting in an increased incidence of infection 6,7. Furthermore, haematological malignancies may lead to antibody deficiency, leucopenia or impaired T-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports suggested that patients with concomitant malignant neoplastic disease, OPCAB surgery has better outcomes and lowered operative mortality because of spared platelet function, less blood loss, and avoidance of infection. [7][8][9] Other than the abovementioned points, a unique situation exists in patients with a brain tumor. Application offpump bypass to these patients is of paramount importance because cardiopulmonary bypass causes tissue edema and consequently increased compression effect of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports suggested that patients with concomitant malignant neoplastic disease, the OPCAB surgery has better outcomes and lowered operative mortality because of spared platelet function, less blood loss, and avoidance of infection. [7][8][9] Other than patients having solitary cancer, patients with a low-grade lymphocytic malignancy (including some types of non-Hodgkin's lymphoma and chronic lymphocytic leukemia) can be referred for coronary bypass surgery if a long-term survival is expected.…”
mentioning
confidence: 99%
“…The majority had coronary artery bypass surgery as well as valvular replacement. Previous studies, showed that cardiac surgery can be performed but carries a high incidence of mortality and morbidity [5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%